(untitled) (Research, Society and Development, 2024)
Introduction: Polio is an acute infectious disease caused by poliovirus, which predominantly affects children, and the only preventive measure is vaccination. However, in 2020, the emergence of the coronavirus disease interrupted all supplementary polio immunization activities, leading to a drop in Brazilian vaccination coverage, from 89.5% in 2018 to 76.7% in 2020. Objective: To analyze polio vaccination coverage by region and by federative unit in Brazil, from 1999 to 2022. Methods: This is an epidemiological study of descriptive analysis, carried out through the collection of annual data on national, regional and federal unit vaccination coverage for the period from 1999 to 2022, made available by the TABNET of the Department of Information and Informatics of the Unified Health System (DATASUS). The selection criteria were performed for statistical purposes and only related to the pólio immunobiological. The data were transferred to an Excel spreadsheet and submitted to statistical analysis. Results: The results showed a pattern of a 3.05% drop in vaccination coverage per year in pre-pandemic years (2017 to 2019), and it is expected that without the pandemic the years 2020 and 2021 would accumulate a drop of 6.10%. However, the pandemic intensified the pattern of decline to 12.44%. Conclusion: The COVID-19 pandemic has posed significant challenges to achieving vaccination goals at the national and regional level.